Intra-Species Variations of Bioactive Compounds of Two Dictyota Species from the Adriatic Sea: Antioxidant, Antimicrobial, Dermatological, Dietary, and Neuroprotective Potential - Ana Martić; Lara Čižmek; Nikolay V. Ul'yanovskii; Tina Paradžik; Lucija Perković; Gabrijela Matijević; Tamara Vujović; Marija Baković; Sanja Babić; Dmitry S. Kosyakov; Polonca Trebše; Rozelindra Čož-Rakovac (MDPI AG, 2023)
The marine environment has a significant impact on life on Earth. Organisms residing in it are vital for the ecosystem but also serve as an inexhaustible source of biologically active compounds. Herein, the biodiversity of two brown seaweeds, Dictyota dichotoma and Dictyota fasciola from the Adriatic Sea, was evaluated. The aim of the study was the determination of differences in compound composition while comparing their activities, including antioxidant, antimicrobial, and enzyme inhibition, in connection to human digestion, dermatology, and neurological disorders. Chemical analysis revealed several terpenoids and steroids as dominant molecules, while fucoxanthin was the main identified pigment in both algae. D. dichotoma had higher protein, carbohydrate, and pigment content. Omega-6 and omega-3 fatty acids were identified, with the highest amount of dihomo-γ-linolenic acid and α-linolenic acid in D. dichotoma. Antimicrobial testing revealed a dose-dependent inhibitory activity of methanolic fraction against Escherichia coli and Staphylococcus aureus. Moderate antioxidant activity was observed for both algae fractions, while the dietary potential was high, especially for the D. fasciola dichloromethane fraction, with inhibition percentages of around 92% for α-amylase and 57% for pancreatic lipase at 0.25 mg/mL. These results suggest that Dictyota species might be a potent source of naturally derived agents for obesity and diabetes.